Exploring Students’ Informal Digital Learning of English (IDLE) and Self-Regulated Language Learning from a Sociocultural Perspective - Fauziah, Fauziah; Diana, Novita (Indonesian TESOL Journal, 2023)
This study investigates the phenomenon of informal digital learning of English (IDLE) among students engaged in independent online learning environments. Focusing on practices for students’ language development, this study explores how students autonomously acquire English language skills through informal digital means and examines the implications. It employs a mixed-methods approach, combining surveys and interviews to collect and analyse data from a diverse group of independent online learners of English (N= 182) from 23 different Indonesian universities. Quantitative data reveals that approximately 45.1% of the variation in self-regulated language learning can be explained with informal digital learning of English identified as one of the predictors. On the other hand, qualitative data findings indicate that students actively engage in IDLE through a variety of digital channels, including social media, online forums, language learning apps, and YouTube tutorials. These informal learning activities encompass a wide range of language skills, from vocabulary acquisition and pronunciation improvement to cultural understanding and conversational proficiency. Implications of this research point to the importance of recognising and harnessing students’ IDLE practices in formal educational settings. Educators and institutions can leverage these insights to design more effective online language learning programmes that incorporate elements of informal digital learning.